The Role of the Supervisor in Implementing Supervision to Enhance the Quality of Student Learning Outcomes Through Continuous Improvement - Ntimuk, Petronela; Achmad Supriyanto; Ali Imron; Sarah M. Zehr (Education Specialist, 2023)
This research explores the role of supervisors, particularly school principals, in improving student learning outcomes through continuous improvement. The study emphasizes the integral role of school principals in educational institutions. The research investigates the three key phases of supervision: planning, implementation, and evaluation. Effective supervision commences with comprehensive planning at the start of the academic year, involving all teachers and school staff. The core of supervised programs lies in their implementation, during which the principal observes teaching, classroom conditions, and student engagement. Subsequently, the evaluation stage involves an analysis of planning and implementation, enabling the identification of strategies and solutions to address issues and achieve continuous improvement. The qualitative methods employed in this research include observation, interviews, and documentation at sekolah menengah pertama katolik (SMPK) Kolese St. Yusup 2 Malang. The results demonstrate that the planning, implementation, and evaluation stages of supervision at SMPK Kolese St. Yusup 2 Malang have successfully adopted a continuous improvement approach. This is evidenced by improvements in teacher effectiveness, social and personality competencies, and student learning outcomes, with notable achievements at local, regional, and national levels. The findings underscore the transformative potential of school principals as agents of change in academic supervision activities.